Kelayakan Finansial dan Nilai Tambah Kacang Goreng Balado AA di Kota Padang - Christanty Febriana; Dang Sri Chaerani; Herda Gusvita (Fakultas Pertanian, Universitas Ekasakti, 2022)
The objectives of this study are 1). Analyzing the financial feasibility of Balado AA fried peanuts in Padang City 2). Analyzing the added value of Balado AA fried peanuts in Padang City. The method used in this research is descriptive method. Respondents in this study were owners of balado AA fried peanuts in Padang Pasir Village, West Padang District. The sampling used in this study was purposive sampling. The types of data to used are qualitative and quantitative. Data analysis was carried out by analyzing the feasibility and added value. Based on the research results, it is found that: 1.) Balado AA fried peanut business in Padang Pasir Village, West Padang District is feasible to be looked at from the R / C ratio value of 2,29; BEP for Rp. 21.837,71 and BEP for volume of 384,34 Kg. 2.) The added value obtained in the agro-industry of Balado AA fried peanuts is an average of Rp. 56.663,45 / kg or a value added ratio of 56,66% with a profit of 58,33%. From the research results it can be suggested: 1). Business owners are expected to maintain the quality of Balado AA Fried Peanuts. The company is advised to improve financial management in the Balado AA Fried Peanut business. 2). Marketing research needs to be carried out to increase the demand for products produced by Balado AA Fried Peanuts, so that it is expected to increase the production and income of entrepreneurs optimally